2005
DOI: 10.1086/426867
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Genital Human Papillomavirus Infection in a Cohort of Closely Followed Adolescent Women

Abstract: Background-We performed a study to better characterize the natural history of genital human papillomavirus (HPV) infection in a cohort of closely followed adolescent women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
267
7
17

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 357 publications
(304 citation statements)
references
References 25 publications
11
267
7
17
Order By: Relevance
“…Similarly a study done among Malaysian women showed that for those who were not sexually active, they thought they did not need the vaccine and preferred to wait before they were vaccinated (Wong, 2008). However, earlier studies carried out abroad showed that the cumulative prevalence for HPV infection among adolescents is as high as 82% (Brown et al, 2005). Thus, vaccination in younger age would provide the effective protection against cervical cancer before the adolescents are exposed to HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a study done among Malaysian women showed that for those who were not sexually active, they thought they did not need the vaccine and preferred to wait before they were vaccinated (Wong, 2008). However, earlier studies carried out abroad showed that the cumulative prevalence for HPV infection among adolescents is as high as 82% (Brown et al, 2005). Thus, vaccination in younger age would provide the effective protection against cervical cancer before the adolescents are exposed to HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…HPV infection is the most common infection among young and sexually active individuals (Weaver, 2006). Rates of HPV infection are highest in adolescent females with a cumulative prevalence rate higher than 80% (Brown et al, 2005). Thus, it is necessary for young women to get protection against HPV infection at an early age.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these HPV infections are found to be transient and only women who harbor persistent high risk HPV infection are at risk of developing cervical lesions. High risk HPV infections (hrHPV) seem to persist longer than infections with low risk HPVs (Franco et al, 1999;Woodman et al, 2001;Guiliano et al, 2002;Richardson et al, 2003;Munoz et al, 2004;Brown et al, 2005). To effectively design cervical cancer prevention strategies, information regarding the incidence, prevalence and clearance of HPV infections in a variety of populations is needed.…”
Section: Introductionmentioning
confidence: 99%